Miloš Wasserbauer’s Work at the Slovak National Theatre in the 50s and Early 60s of the 20th Century - Kysová Šárka Havlíčková (Slovenské divadlo)
The article examines the work of opera director Miloš Wasserbauer during the 50s and at the beginning of the 60s of the 20th century in the Slovak National Theatre. Focusing on the staging of new Slovak operas Ján Cikker’s Juro Jánošík and Beg Bajazid, and Eugen Suchoň’s Svätopluk. The author analyses Wasserbauer’s approach to the productions and Slovak staging tradition from the perspective of the Czech director and the critical reflection of the performances. Special attention is paid to the conceptualisation of Slovak national feeling in the corpus of archive materials.